Study on the Anti-tumor Mechanisms of Heat Shock Protein 72/alpha-fetoprotein Epitope Peptide Complex Against Hepatocellular Carcinoma Cell Hepa1-6. Issue 5 (April 2019) - Xu, Bing; Wang, Xiaoping; Lin, Huanping
Abstract: Objective: Mice immunized with heat shock protein 72 (HSP72)–alpha-fetoprotein (AFP) epitope peptide complex were used to study whether the complex has specific anti-tumor immune effect against AFP tumor. Methods: Kunming mice were immunized subcutaneously with HSP72-AFP peptide complex, and mice were immunized with AFP polypeptide and HSP72, respectively. The serum IFN-γ levels in mice after immunization were detected by ELISA. The killing effect of lymphocytes on hepatic cancer Hepal-6 cells was detected by MTT assay. The immune effect of protein complex was evaluated by tumor burden test in mice. Results: The serum IFN-r levels and the killing effect of lymphocytes on Hepal-6 cells in HSP72-AFP peptide complex group were significantly higher than those in AFP polypeptide and HSP72 group (P<0.01). The tumor volume in HSP72-AFP polypeptide complex group was also significantly smaller than that of the AFP polypeptide and HSP72 immunized groups (P<0.01). Conclusion: The HSP72-AFP polypeptide complex vaccine can induce tumor-specific mice to produce specific cellular immunity against AFP tumors, and its killing effect on tumor cells is significantly better than that of the single polypeptide purified vaccine. The surface HSP72-AFP polypeptide complex can induce effective anti-tumor immunity in mice.